The Destiny of Glucose from a MicroRNA Perspective - Mirra, Paola; Nigro, Cecilia; Prevenzano, Immacolata; Leone, Alessia; Raciti, Gregory Alexander; Formisano, Pietro; Beguinot, Francesco; Miele, Claudia (Frontiers in Endocrinology, 2018)
Glucose serves as a primary, and for some tissues the unique, fuel source in order to generate and maintain the biological functions. Hyperglycemia is a hallmark of type 2 diabetes and is the direct consequence of perturbations in the glucose homeostasis. Insulin resistance, referred to as a reduced response of target tissues to the hormone, contributes to the development of hyperglycemia. The molecular mechanisms responsible for the altered glucose homeostasis are numerous and not completely understood. microRNAs are now recognized as regulators of the lipid and glucose metabolism and are involved in the onset of metabolic diseases. Indeed, these small non-coding RNA molecules operate in the RNA silencing and post-transcriptional regulation of gene expression and may modulate the levels of kinases and enzymes in the glucose metabolism. Therefore, a better characterization of the function of microRNAs and a deeper understanding of their role in disease may represent a fundamental step towards innovative treatments addressing the causes, not only the symptoms, of hyperglycemia, using approaches aimed at restoring either microRNAs or their specific targets. In this review, we outline the current understanding regarding the impact of microRNAs in the glucose metabolism and highlight the need for further research focused on altered key kinases and enzymes in metabolic diseases.